2020
DOI: 10.1007/s10552-020-01362-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of diet and physical activity interventions amongst adults attending colorectal and breast cancer screening: a systematic review and meta-analysis

Abstract: Purpose To estimate the effectiveness of tailored physical activity and dietary interventions amongst adults attending colorectal and breast cancer screening. Methods Five literature databases were systematically searched to identify randomised controlled trials (RCTs) of tailored physical activity and/or dietary interventions with follow-up support initiated through colorectal and breast cancer screening programmes. Outcomes included markers of body fatness, physical activity, and dietary intake. Mean diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…There is an increasing body of research suggesting that cancer screening programmes provide opportunities for lifestyle change programmes. 22 The current work on implementation science was designed to promote the systematic uptake of previously reported research into routine practice. 23 The findings demonstrated that engagement, programme uptake and retention were significantly lower than that obtained from the original BeWEL RCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an increasing body of research suggesting that cancer screening programmes provide opportunities for lifestyle change programmes. 22 The current work on implementation science was designed to promote the systematic uptake of previously reported research into routine practice. 23 The findings demonstrated that engagement, programme uptake and retention were significantly lower than that obtained from the original BeWEL RCT.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing body of research suggesting that cancer screening programmes provide opportunities for lifestyle change programmes 22 . The current work on implementation science was designed to promote the systematic uptake of previously reported research into routine practice 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Relevant peer-reviewed studies published from January 2010 to August 2022 were included, as genetic counseling related to cancer risk only began in the late 1990s, and published studies on behavioral risks in these populations did not begin to appear until the 2010s [ 18 ]. References cited in systematic reviews evaluating lifestyle interventions [ 23 , 31 , 32 ] in other populations were screened for additional articles which might have been overlooked. The website clinicaltrials.gov was also checked for any published protocols or feasibility studies.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review [ 22 ] of lifestyle behaviors in patients receiving genetic counselling found that communicating the risk of cancer due to genetic alteration has little impact on lifestyle behaviors such as smoking, diet, or physical activity. However, a review evaluating interventions during colorectal and breast cancer screening found that behavioral interventions can promote increased physical activity and dietary modifications [ 23 ]. The same tendency has been observed in cancer survivors, who are motivated to engage in interventions following treatment; however, these changes are not normally sustained long term [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most prevalent cancer in women, with a global incidence of 2.3 million cases in 2020. Overall mortality in the same year recorded 685,000 deaths [ 1 ], although prevention, based on mammographic X-ray screening, has been a long-standing effort [ 2 , 3 , 4 , 5 , 6 ]. Patients harboring a germline BRCA1 or BRCA2 mutation suffer from an autosomal dominant genetic disorder in these tumor suppressor genes [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%